Simple and sensitive assay for quantification of oseltamivir and its active metabolite oseltamivir carboxylate in human plasma using high-performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry: improved applicability to pharmacokinetic study - Hu, Zhe-Yi (2012)
Although liquid chromatography/electrospray ionization tandem mass spectrometry-based assays have been reported for the measurement of the antiviral oseltamivir (OS) in human samples, these assays either involve complicated sample pretreatment or lack sensitivity. Here we introduce a straightforward approach to improve the assay performance for OS and its metabolite oseltamivir carboxylate (OSC) in human plasma. A very low concentration of mobile phase modifier can improve the ionization efficiency of both analytes, thus enabling a high sensitivity without any matrix effect. The fast LC gradient further increases the sensitivity by narrowing the peak width (6–9 seconds) and eluting the analytes at higher organic content. The increased ionization efficiency and minimized matrix effects enabled us to introduce a one-step protein precipitation for sample clean-up without compromising the sensitivity. The lower limit of quantification was 0.34 ng/mL for both analytes, which was at least 3 times more sensitive than published assays that involve complicated sample pretreatment. The assay involves measurement of analytes and their stable-isotope internal standards in small-volume (30-µL) plasma. Sodium fluoride was utilized to prevent the hydrolysis of OS during and after sampling. The calibration curve was linear over the range of 0.34–1000 ng/mL. Accuracy was 95–110% and the precision was 2.2–11.0%. This method was applied successfully to the human pharmacokinetic study of OS, and can estimate the relevant pharmacokinetic parameters of OS with more accuracy. The approach utilized in the optimization of assay performance can be extended to the measurement of other drugs in biomatrices.